Pathogenesis of Infectious Diarrhea - John Stephen (Canadian Journal of Gastroenterology)
A brief overview of some of the main features involved in normal physiological bi-directional absorption and secretion of fluid in the gut is given, including the nature and cellular location of key enzymes, ion pumps, symports, antiports and diffusion channels; the microanatomy of intestinal villous vasculature and the dynamics of villus blood flow, which together generate hypertonic zones in villus tip regions; and the production, differentiation, escalator movement (from crypt to villus tip) and subsequent shedding of intestinal epithelial cells. (Neural and hormonal mechanisms that regulate normal mucosal ion transport are not discussed.) The manner in which Vibrio cholerae, several pathotypes of Escherichia coli, several Salmonella serotypes, rotavirus, Campylobacter species, Shigella dysenteriae, Yersinia species and Clostridium difficile perturb these mechanisms and cause diarrhea, is discussed. Throughout the article, the main emphasis is on experimental studies designed to elucidate biological mechanisms and (where relevant) the microbial determinants responsible for diarrheal disease. Allusions are also made to the involvement of host responses such as the inflammatory response, the production and release of potent cytokines and accelerated homeostatic responses (such as increased rates of crypt cell division seen in some infections), and the role that they play in pathophysiological fluid secretion.